Developing Picture Story Book Media for Building the Self-Awareness of Early Childhood Children - Febri Yuridnir Rahimah; Rita Eka Izzaty (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
This research aimed to develop a picture story book media feasible for building the self-awareness of early childhood children and reveal the effectiveness of the developed picture story book media.This research and development (RD) referred to the development procedure developed by Borg and Gall. The data analysis used the qualitative anaylisis and independent sample t-test. Sampling technique used purposive sampling. The preliminary field testing sujects consisted of 6 students of Al Amien Kindergarten. The main field testing subjects consisted of 30 students of Al Amien Kindergarten. The operational field testing subjects consisted of 40 students of ABA Karangmalang Kindergarten. The result of this research was as follows. First, the developed picture story book media was feasible to be used for building the self-awareness of early childhood students. It was proven from the result of media and material validation, also the result from teacher and children questionnaire. Second, the developed picture story book media was effective in building the self-awareness of 5 – 6 years old students significantly.